Daya Tarik Wisata Pascabencana Erupsi Gunungapi Sinabung di Kabupaten Karo, Sumatera Utara - Liyushiana Liyushiana; Putri Rizkiyah; Herman Herman (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2019)
Karo Regency is one of the main tourism destinations in North Sumatra Province which is famous for its natural beauty and strategic location as one of the districts that inhabits Lake Toba's super priority destinations. But the fact that in the Karo District over the past decade there has been a Sinabung volcano disaster that has disrupted and affected the tourism sektor therefore, this study aims to examine the existing conditions of the main tourist attractions in Karo District and the impact of the eruption of the Sinabung volcano on these tourist attractions. This study uses descriptive qualitative research methods using observation data collection techniques, focus group discussions, and desk research. It examines 7 (seven) main tourist attractions in terms of attractions, accessibility, and amenities. Those seven tourist attractions are: Gundaling Hill, Penatapan, Lumbini Nature Park, Lau Kawar Lake, Sipiso-piso Waterfall, Berastagi Fruit Market and Karo Heritage Museum. It was concluded that Lake Lau Kawar is one of the tourist attractions with the most severe impact of the eruption of Mount Sinabung. On the other hand, traders in the Berastagi fruit market have also become more creative in marketing their products not only limited to natural products whose quality and quantity have declined since the eruption of the Mt. Sinabung. The effect of the Sinabung volcano eruption is not too significant on tourism infrastructure and amenities, but the improvement of the two components is important because the conditions of some facilities, especially toilets, have not met the standards. Keywords: Tourist attractions, volcano disaster